1995
DOI: 10.1046/j.1471-4159.1995.64062552.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide Induces a Long‐Lasting Inhibition of the Ca2+‐Dependent Glutamate Release in Cerebrocortical Synaptosomes Without Interfering with Cytosolic Ca2+

Abstract: We studied the action of H2O2 on the exocytosis of glutamate by cerebrocortical synaptosomes. The treatment of synaptosomes with H2O2 (50–150 µM) for a few minutes results in a long‐lasting depression of the Ca2+‐dependent exocytosis of glutamate, induced by KCl or by the K+‐channel inhibitor 4‐aminopyridine. The energy state of synaptosomes, as judged by the level of phosphocreatine and the ATP/ADP ratio, was not affected by H2O2, although a transient decrease was observed after the treatment. H2O2 did not pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 39 publications
3
22
0
Order By: Relevance
“…Consistent with previous reports (Zoccarato et al 1995;Tretter and Adam-Vizi 1996) we found in this study that hydrogen peroxide alone failed to induce release of glutamate (Figs 1 and 2). The dominant effect of H 2 O 2 itself on the glutamate metabolism/release is an enhanced utilization of glutamate as a metabolite within nerve terminals .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Consistent with previous reports (Zoccarato et al 1995;Tretter and Adam-Vizi 1996) we found in this study that hydrogen peroxide alone failed to induce release of glutamate (Figs 1 and 2). The dominant effect of H 2 O 2 itself on the glutamate metabolism/release is an enhanced utilization of glutamate as a metabolite within nerve terminals .…”
Section: Discussionsupporting
confidence: 94%
“…An increased basal release of glutamate from synaptosomes was reported by Gilman et al (1992) whereas no change in the resting release by H 2 O 2 was found in other studies (Zoccarato et al 1995;Tretter and Adam-Vizi 1996). Furthermore, a long-lasting depression of the depolarization-induced glutamate release was also reported (Zoccarato et al 1995). In view of the release of glutamate during oxidative stress, a recent observation that under H 2 O 2 -induced oxidative stress, glutamate is used as an alternative metabolite decreasing the glutamate reserves in nerve terminals should also be considered.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Oxidative stress inhibits neurotransmitter release (Gilman et al 1992;Zoccarato et al 1995;Zoccarato and Alexandre 1996;Chen et al 2001;Giniatullin and Giniatullin 2003). Moreover, oxidative stress and impaired synaptic transmission are correlates of aging and the early stages of neurodegenerative disease (Keating 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the finding that hydrogen peroxide inhibits glutamate release without affecting cytosolic Ca 2? levels (Zoccarato et al 1995) suggests that oxidative stress may inhibit neurotransmitter release by blocking the assembly and/or function of the ternary SNARE [synaptic N-ethylmaleimide-sensitive factor attachment protein (SNAP) receptor] complex required for synaptic vesicle docking and fusion. Moreover, the results of one study demonstrated that assembly of the SNARE complex from recombinant proteins in vitro was particularly sensitive to the prior exposure to H 2 O 2 /Fe 2?…”
Section: Introductionmentioning
confidence: 99%